Use of Oral Misoprostol for the Treatment of Incomplete Abortion - Kayastha, S; Tuladhar, H; Gurung, S; Jaishe, S (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This study was done to assess the feasibility and acceptability of use of Misoprostol 600 mcg orally for treatment of incomplete abortion. Methods: A hospital based prospective study was carried out in the Department of Obstetrics and Gynaecology of Nepal Medical College Teaching Hospital from 1st November 2010 to 30th May 2013. All cases of first trimester incomplete abortion diagnosed clinically or by ultrasonogram were included in the study. They were given 600 mcg of Misoprostol orally. They were sent home, with advice to come for follow up after one week. Routine Ultrasound was carried out on follow up visit to confirm complete abortion. The side effects, complications and patient satisfaction was assessed and recorded. Results: Out of 86 patients, 8.1% (7) had to undergo surgical evacuation. So the success rate was 91.9% (79 cases). All the cases which needed evacuation were of higher gestation, that is, nine weeks or more. The commonest side effect was severe abdominal pain (81.4%). Three cases required emergency surgical evacuation within 24 hours due heavy bleeding. Conclusions: It is feasible and acceptable to use Misoprostol orally for medical evacuation, especially in earlier gestation of first trimester incomplete abortion. Side effects were common but were acceptable and tolerable by the patients. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 2 / Issue 16 / July-Dec, 2013 / 30-33 DOI: http://dx.doi.org/10.3126/njog.v8i2.9766